Implementing Generative AI Training to Enhance Creative Content Competencies and Digital Productivity at the Media Prima Mojokerto Course and Training Institute - Ahmad Yahya Hamiduddin; Masruchan Masruchan; Dwi Wahyuni (Civiliza Publishing, 2026)
The rapid advancement of Generative Artificial Intelligence (Generative AI) has transformed the way digital content is created and managed across various sectors, including education and vocational training. However, many participants at the Media Prima Mojokerto Course and Training Institute still have limited knowledge and practical skills in utilizing AI-based tools to support creative content production and improve digital productivity. This community engagement program aimed to enhance participants' competencies through a structured Generative AI training program. The implementation methods consisted of needs assessment, lectures, demonstrations, hands-on practice, mentoring, and evaluation. The training introduced participants to various Generative AI applications for text generation, image creation, presentation design, and productivity enhancement. Evaluation was conducted using pre-tests, post-tests, practical assignments, and participant satisfaction questionnaires. The results indicated a significant improvement in participants' understanding and practical skills in utilizing Generative AI technologies. Participants demonstrated increased creativity in developing digital content, improved efficiency in completing digital tasks, and greater confidence in adopting AI tools for educational and professional purposes. Furthermore, the training fostered participants' awareness of ethical AI use and responsible digital content creation. Therefore, the implementation of Generative AI training proved effective in strengthening creative content competencies and enhancing digital productivity among participants at the Media Prima Mojokerto Course and Training Institute. This program is expected to serve as a sustainable model for improving digital literacy and AI competencies in vocational education and training institutions.